CORRELATION OF TG/HDL-C RATIO AND TyG INDEX WITH C-REACTIVE PROTEIN IN IMPAIRED FASTING GLUCOSE SUBJECTS - Adam, Fabiola Maureen Shinta; Fahly, Rizal; Aman, Andi Makbul; Rasyid, Haerani; Bakri, Syakib (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Prediabetes is an insulin resistant (IR) condition. The TG/HDL-C ratio and TyG index were associated with prediabetes and IR which are related to cardiovascular disease (CVD). HS-CRP is a marker of inflammation that is closely related to CVD. The aim of this study is to determine the correlation between TG/HDL-C ratio and TyG index with HS-CRP as a marker of chronic inflammation in impaired fasting glucose (IFG). METHODOLOGY Research subjects were taken from Makassar Lipid and Diabetes Study, an observational study which involved 92 prediabetic subjects aged 18-70 years old in Makassar City, Indonesia between January to April 2022. Triglyceride, HDL-C, FPG, and HS-CRP were examined. Level of HS- CRP >3-10 mg/L defined as a high risk of CVD. Impaired Fasting Glucose defined as fasting plasma glucose 100-125 mg/dL. Statistical analyses used were Kruskal-Wallis and Chi-Square tests. RESULTS The mean TG/HDL-C ratio was 4.88, TyG index was 4.92, and HS-CRP level was 4.53 ± 2.91 mg/L. The Chi Square test showed that there was no significant difference between TG/HDL-C ratio and TyG Index with high risk group of CVD (HS-CRP >3-10 mg/dL) among IFG subjects with p= 0.383 and p=0.584, respectively. CONCLUSION Our results indicate that there is no statistically significant relationship between TG/HDL-C ratio and TyG index with HS-CRP in prediabetic IFG subjects.